¿El nuevo Comas? Trayectorias residenciales de los residentes de los edificios multifamiliares de altura en El Retablo, Comas - Huaroto Casas, Diego Ignacio (2024)
The presence of high-rise multifamily housing in the central areas of Latin American cities has been a trend since the 1980s, driven by the global economic liberalization. In Metropolitan Lima, this boom is evident in the construction of such housing in central districts like Jesús María, Lince, Breña, San Isidro, Miraflores, and others. However, over the past 15 years, this trend has extended to the city’s periphery. Comas is one of the districts where high-rise apartments have appeared, particularly due to projects in the El Retablo area on the former Aeroclub de Collique site. This suggests changes in both urban development in the district and in the expectations and experiences of citizens regarding this new type of housing. This study will focus on the latter, specifically investigating the residential trajectories of current residents of the El Retablo condominiums in Comas and how their expectations and desires influenced their decision to move to this new type of housing. The methodology is qualitative: interviews were conducted with residents from various condominiums in the area for subsequent analysis. The main reasons for moving to these condominiums were found to be the low cost of the apartments and the desire to own something. These reasons were influenced by their previous residential trajectories